2019
DOI: 10.3389/fpsyg.2019.02360
|View full text |Cite
|
Sign up to set email alerts
|

Major Incongruence and Occupational Engagement: A Moderated Mediation Model of Career Distress and Outcome Expectation

Abstract: This study investigated the possible mediation of career distress in the relationship between major incongruence and occupational engagement and whether this mediation depends on the degree of outcome expectation. Moderated mediation analysis was tested on a sample of 346 Korean undergraduate students. The results indicated that career distress mediated the relationship between major incongruence and occupational engagement. Moreover, the negative indirect effect of major incongruence on occupational engagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…However, later studies have shown the opposite relation, indicating that there is a reciprocal relationship between self-efficacy and expectation outcomes (e.g., Corcoran [64]; Flores, et al [65]). Related studies showed that career outcome expectations were positively correlated with the occupational engagement of undergraduate students in Korea [66], which was supported by expectancy-value theory [67]. Students' expectancies and goals for learning were found to be determinants of their selfefficacy and performance [67].…”
Section: The Direct and Indirect Relationships Of Engineering Career Outcome Expectations With Engineering Skill Self-efficacy And Losmentioning
confidence: 79%
“…However, later studies have shown the opposite relation, indicating that there is a reciprocal relationship between self-efficacy and expectation outcomes (e.g., Corcoran [64]; Flores, et al [65]). Related studies showed that career outcome expectations were positively correlated with the occupational engagement of undergraduate students in Korea [66], which was supported by expectancy-value theory [67]. Students' expectancies and goals for learning were found to be determinants of their selfefficacy and performance [67].…”
Section: The Direct and Indirect Relationships Of Engineering Career Outcome Expectations With Engineering Skill Self-efficacy And Losmentioning
confidence: 79%
“…It is common in young adults and has become an important reason for them to attend career counselling (S ¸ensoy & Siyez, 2019). High career distress has been associated, in turn, with lower occupational engagement and future career expectations (Kim & Lee, 2019) and poorer psychological and subjective wellbeing (Arslan et al, 2020). In this study, we distinguished between career distress related to uncertainty about one's career future (i.e.…”
Section: Explanatory Mechanism Of Negative Emotionsmentioning
confidence: 99%